Pengelolaan Zakat di Baznas Kabupaten Lombok Timur dalam Perspektif Total Quality Management - Abd Hayyi; Muh. Salahuddin; Muh. Azkar (PALAPA, 2023)
Zakat is an important instrument in alleviating poverty, considering the large potential of zakat both locally and nationally. This law stipulates that zakat management aims to increase the effectiveness and efficiency of services in zakat management and increase the benefits of zakat to realize community welfare and reduce poverty. This research aims to find out how to apply the principles of customer focus, process improvement, and total involvement for the components of leadership, employee loyalty, and partner involvement. The research method uses descriptive qualitative methods with a case study approach data collection techniques through observation, interviews, and documentation. Primary data comes from Baznas leaders and implementers, while secondary data is collected from East Lombok Regency Baznas zakat management documents and related research or scientific work. Data analysis was carried out in three stages, namely data reduction, data display, and conclusion drawing/verification. The findings from this research show that: 1. Baznas East Lombok Regency has provided good services to Muzakki and Mustahiq. 2. In terms of improving the Baznas process, East Lombok Regency has carried out improvement steps every year which cover four existing areas, namely process improvement in the field of collection, process improvement in the distribution and utilization field, process improvement in the field of planning and reporting and process improvement in the field of administration, HR and general fields. 3. Regarding total involvement, Baznas East Lombok Regency has involved leaders, amilin, and partners in managing zakat.